Effects of Different Particle Size Distribution and Insoluble Dietary Fiber Content from Pomelo by-Products on the Quality Characteristics of Rice Noodle Products - Pichaiyongvongdee, Suwanna; Foophow, Tita; Rasamipaiboon, Nujira; Youdee, Piyawan (Journal of Food Health and Bioenvironmental Science, 2023)
Rice noodles are a widely consumed food in Asia, including in Thailand. Nevertheless, this popular food is high in carbohydrates, but low in dietary fiber. Pomelo by-products (PBP) are a highly insoluble dietary fiber (IDF) source that has been investigated for fiber-fortified rice noodles with health benefits. This study was conducted to prove the effects of IDF in PBP at different levels (10 and 12.5%) of the rice flour and different particle size distributions (180 and 150 μm) on the moisture content, water activity, cooking weight, cooking loss, textural and sensory evaluation. The addition of IDF-PBP to rice noodles was found to have significant (p<0.05) effects on the colors of a*, b*, while cooking weights were increased in all samples. Cooking loss and tensile strength also decreased as compared to the control. The moisture content and water activity of rice noodles were between 8.66-9.14% and 0.32-0.36, respectively. When considering the addition of IDF-PBP at 10 and 12.5%, the findings revealed that the sample was not significantly different (p>0.05) in the cooking weight. However, when the particle size was reduced, the cooking weight increased. Cooking loss decreased when IDF-PBP was increased, and the particle size was reduced. The texture of the particle size distribution was 180 and 150 μm at levels 10% in tensile strength and showed not significant difference (p>0.05) as compared to the control rice noodles. Rice noodles with 10% IDF-PBP particle size distribution 150 μm showed the highest overall acceptability in sensory evaluation. The results revealed that adding IDF-PBP to rice noodles increased the total dietary fiber content at 9.44% and the insoluble dietary fiber content at 8.71% as compared to the control rice noodles. Based on the results, the addition of IDF-PBP to rice noodles can lead consumers to conclude that the product is healthy.